The Role of Parents in Appliying Discipline to Children in A Pandemic Period - Irena Dara Melfia (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
In this era of the COVID-19 pandemic, children are learning online. Therefore, all childrenactivities are also carried out at home, so parents certainly have a big role in studentactivitiesathome,oneofwhichisdiscipline.Disciplineis anaspectthat mustbe instilled in children from anearly age so that later they can get used to ituntil adulthood.Withoutdiscipline,thechildwillbecome someone who has no direction and purpose. Therefore, discipline is very important to beinstilled. In this study,the subjects usedwere parentsand children.The purpose ofthis research isto findoutthe role of parentsinapplyingdisciplinetochildren.Thedatacollectionmethodusedisintheform of a literature study. Therefore, data is obtained about the role of parents in applyingdiscipline to children inthe pandemic era.